Zenker's diverticulum treated via per-oral endoscopic myotomy. Issue 2 (2nd April 2020) - Ebrahim, Ahmed; Leeds, Steven G.; Clothier, Jessica S.; Ward, Marc A.
Abstract: Zenker's diverticulum (ZD) is a rare disorder of the esophagus that occurs in approximately 0.1% of the population. Recently, new minimally invasive techniques have been used to treat ZD. Similar to a per-oral endoscopic myotomy (POEM) for achalasia, ZD can be treated using an endoscopic myotomy with a standard endoscope. This technique offers the benefit of a purely endoscopic procedure without the added morbidity associated with the traditional open technique. This is a description of the first per-oral endoscopic myotomy for Zenker's diverticulum (Z-POEM) performed at Baylor University Medical Center at Dallas.